P008 Clinical Applicability of Anti-CdtB and Anti-Vinculin Antibodies to Diagnose Superimposed Irritable Bowel Syndrome in Inflammatory Bowel Disease Patients. (December 2019) - Barros, Luísa; Pimentel, Mark; Morales, Walter; Leite, Gabriela; Mathur, Ruchi; Sanchez, Maritza; Damião, Adérson; Azevedo, Matheus; Queiroz, Natália; Carlos, Alexandre; Milani, Luciane; Oba, Jane; et al.
Abstract : BACKGROUND: A great proportion of Inflammatory Bowel Disease (IBD) patients exhibit persistent gastrointestinal symptoms such as diarrhea and abdominal pain that are not always related to mucosal inflammation. In this setting, irritable bowel syndrome (IBS) is the most frequent superimposed condition and ROME IV criteria have limited diagnostic accuracy. Recently, anti-CdtB and anti-vinculin, which are derived from the underlying pathophysiology of post-infectious IBS, were proposed to rule-in IBS and discriminate IBS from IBD. The applicability of this strategy may be hampered by the cross-reactivity of vinculin and cytoskeleton Giardia antigens and by data scarcity in cases of concomitant IBD-IBS as well. The aim of this study was to assess the role of an antibody-based strategy in patients with both conditions in a high prevalence region of Giardia lamblia infection. METHODS: Patients were enrolled into 4 groups: (i) active IBD patients with chronic diarrhea (more than 3 bowel movements/day) (n = 44); (ii) IBD-IBS patients (defined by quiescent mucosal inflammation SES-CD ⩽ 2 or Mayo score <= 1 and chronic diarrhea) (n = 25); (iii) IBS predominant diarrhea patients (n = 45); (iv) asymptomatic individuals who underwent colorectal screening colonoscopy (n = 46). Exclusion criteria were: other intestinal diseases, previous abdominal surgery or neoplasia, corticosteroids less than 6 months prior to inclusion, HIV infection. All blood samples were collected at the time of colonoscopy and serum levels of anti-CdtB/anti-vinculin antibodies were determined by enzyme-linked immunosorbent assay. RESULTS: Of 160 subjects the mean age of active IBD patients was 39.5 years, whereas 46.5 years in the overlapping IBD-IBS group, and 39.5 in the IBS-D group; 53.6% (37/69) of total IBD patients had Crohn`s disease. The mean value of the optical density for anti-CdtB was 0.71 ± 0.48 in active IBD, 0.71 ± 0.43 in IBD-IBS patients, 0.70 ± 0.44 in IBS-D and 0.85 ± 0.72 in controls, but no statistical differences were observed between groups ( p = 0.95). IBD-IBS subjects had a trend to have higher levels of anti-vinculin 1.68 ± 1.04 when compared to active IBD 1.50 ± 0.81, IBS-D 1.50 ± 0.94 and controls 1.63 ± 0.9, without significant differences ( p = 0.76). Considering the cut-off point of 1.56 for anti-CdtB and 1.60 for anti-vinculin reported in literature, the frequency of seropositive cases were, respectively: active IBD n = 3 (6.8%) and n = 21 (27.7%); quiescent IBD n = 0 and n = 12 (48%); IBS-D n = 3 (6.6%) and n = 19 (42.2%); controls n = 5 (10.8%) and n = 23 (50%). CONCLUSION(S): We did not find distinct levels of either anti-CdtB or anti-vinculin among active or quiescent IBD, IBS-D and healthy controls. Trend for higher anti-vinculin antibodies titers was observed in IBD-IBS. Thus, IBS diagnosis in IBD patients remains cumbersome in clinical practice.